Current perspectives on the use of stem cells in plastic surgery (Research, Society and Development, 2022)
Adult stem cells, especially mesenchymal ones, have the ability to multiply and differentiate into other tissues, which is promising when dealing with the area of cell therapy. Furthermore, stem cells derived from adipose tissue (ASCs), which are multipotent and have the ability to differentiate into mesenchymal cells, are highly efficient in repair and aesthetic surgeries, mainly due to their high healing process, as they have anti-inflammatory effects. -inflammatory and immunosuppressive. In addition, adipose tissue presents itself as the best way to deal with this subject, as it has minimal morbidity and has high capacity for in vitro cell production. Despite being a great advance in aesthetic and restorative medicine, there are controversies regarding the use of this procedure, such as the safety of the material used. Thus, more comprehensive studies with scientific evidence are still needed.